Analisis Kelayakan Bisnis Usaha T-Shirt Alclothes Ditinjau dari Aspek Pasar, Keuangan, Teknis, dan Sumber Daya Manusia - Aldi Maulana Nugroho; Hani Humaeriyah (INDO PUBLISHING, 2026)
This study aims to analyze the feasibility of the T-Shirt ALCLOTHES business as a local fashion brand by examining market aspects, consumer behavior, human resources, technical operations, and financial performance. The research employs a quantitative descriptive approach through a survey of ten respondents and financial analysis including cost calculation, revenue estimation, and Break Even Point analysis. The results indicate that the product receives positive responses from consumers, particularly in terms of design, quality, and price suitability, and financially generates a net profit of IDR 3,200,000 per month with sales exceeding the break-even point of 97 units. The simple organizational structure, controlled production process, and utilization of digital media further support the business feasibility. Based on these findings, the T-Shirt ALCLOTHES business is considered feasible to operate and develop sustainably.